2016
DOI: 10.1016/j.ypmed.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring risk factors for current cigarette smoking in a U.S. nationally representative sample

Abstract: Introduction Relatively little has been reported characterizing cumulative risk associated with co-occurring risk factors for cigarette smoking. The purpose of the present study was to address that knowledge gap in a U.S. nationally representative sample. Methods Data were obtained from 114,426 adults (≥ 18 years) in the U.S. National Survey on Drug Use and Health (years 2011–13). Multiple logistic regression and classification and regression tree (CART) modeling were used to examine risk of current smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 30 publications
3
56
1
Order By: Relevance
“…Thirteen studies were identified that examined current or lifetime smoking by AUD and/or SUD diagnosis (see Table 3): ten studies of adults 19,2130 and two studies of adolescents 31,32 . The majority of studies (n =8) were conducted in the U.S. with five of those studies using the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies were identified that examined current or lifetime smoking by AUD and/or SUD diagnosis (see Table 3): ten studies of adults 19,2130 and two studies of adolescents 31,32 . The majority of studies (n =8) were conducted in the U.S. with five of those studies using the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al 28 and Higgins et al 30 were the only two studies that were identified as reporting analyses of smoking and AUDs/SUDs by demographics. Higgins et al 30 found no significant two-way interactions of AUD or SUD and smoking by gender, age, or race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…In several instances, poverty seemed to exacerbate the urban/rural differences; this finding is consistent with other tobacco research showing that risk factors can have additive and interactive effects. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Smoking prevalence is 25% for persons with anxiety disorders, 30% for those with depressive disorders (Grant et al, 2004), and 50–80% for those with schizophrenia (Prochaska et al, 2008; Schroeder, 2009). Lasser et al (2000) estimated that 44% of all cigarettes smoked in the U.S. were consumed by persons with mental health diagnoses, and Higgins et al (2016) estimated that 14% of all U.S. smokers are persons with drug and/or alcohol abuse problems.…”
Section: Introductionmentioning
confidence: 99%